2014
DOI: 10.1371/journal.pone.0100685
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Nrf2 Protects against Triptolide-Induced Hepatotoxicity

Abstract: Triptolide, the major active component of Tripterygium wilfordii Hook f. (TWHF), has a wide range of pharmacological activities. However, the toxicities of triptolide, particularly the hepatotoxicity, limit its clinical application. The hepatotoxicity of triptolide has not been well characterized yet. The aim of this study was to investigate the role of NF-E2-related factor 2 (Nrf2) in triptolide-induced toxicity and whether activation of Nrf2 could protect against triptolide-induced hepatotoxicity. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
68
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 26 publications
2
68
1
Order By: Relevance
“…Sulforaphane is known to activate Nrf-2 by interacting with the cysteine residues of Keap1, which is responsible for Nrf-2 ubiquitination (Hu, Eggler, Mesecar, & van Breemen, 2011;Li, Paonessa, & Zhang, 2012). Multiple studies have shown that sulforaphane has remarkable health benefits, including cancer chemoprevention (Tortorella, Royce, Licciardi, & Karagiannis, 2015), avoidance of ischaemia/reperfusion injury (Pan et al, 2014), diabetes (Bhakkiyalakshmi, Sireesh, Rajaguru, Paulmurugan, & Ramkumar, 2015), neurotoxicity (Lee, Jeong, & Park, 2014) and hepatotoxicity (Li et al, 2014). Although a few reports show the effect of sulforaphane mediated activation of Nrf-2 pathway on T cell responses (Geisel et al, 2014), the underlying mechanisms are not completely worked out.…”
Section: Discussionmentioning
confidence: 99%
“…Sulforaphane is known to activate Nrf-2 by interacting with the cysteine residues of Keap1, which is responsible for Nrf-2 ubiquitination (Hu, Eggler, Mesecar, & van Breemen, 2011;Li, Paonessa, & Zhang, 2012). Multiple studies have shown that sulforaphane has remarkable health benefits, including cancer chemoprevention (Tortorella, Royce, Licciardi, & Karagiannis, 2015), avoidance of ischaemia/reperfusion injury (Pan et al, 2014), diabetes (Bhakkiyalakshmi, Sireesh, Rajaguru, Paulmurugan, & Ramkumar, 2015), neurotoxicity (Lee, Jeong, & Park, 2014) and hepatotoxicity (Li et al, 2014). Although a few reports show the effect of sulforaphane mediated activation of Nrf-2 pathway on T cell responses (Geisel et al, 2014), the underlying mechanisms are not completely worked out.…”
Section: Discussionmentioning
confidence: 99%
“…Among these are attenuation by sulforaphane of the cytotoxicity of a number of oxidizers (including menadione, tert-butyl hydroperoxide, 4-hydroxynonenal, dexamethasone, peroxynitrile, gentamycin, and amyloid-b [25][26][27][28][29][30][31][32][33][34][35], while inducing increased expression of QR, NQO1, HO-1, Tr1, and glutathione in human retinal pigment epithelial cells, neuroblastoma cells, osteoblasts, keratinocytes, endothelial cells, and the renal cortex [33][34][35][36][37][38][39][40]. Oral sulforaphane has increased hepatocyte expression of superoxide dismutase, catalase, GST, GPx2, NQO1, HO-1, and glutathione in mice [41] and has increased nasal cell expression of GST, NQO1, and HO-1 [42] and jejunal enterocyte expression of GST [9] in humans. The observations that sulforaphane down-regulates the expression of the phase 1 enzymes, cytochrome P450 (CYP), family 3, subfamily A, polypeptide 4 (CYP3 A4, a major deactivator of pharmaceutical drugs [43]), CYP, family 4, subfamily A isozymes (CYP4 A isozymes, convert arachidonic acid to vasoconstricting 19-and 20-hydroxyeicosatetraenoic acids [44]), and epoxide hydrolase (converts vasodilating epoxyeicosatetraenoic acid metabolites of arachidonic acid into inactive dihydroxy-eicosatrienoic acids [44]), while up-regulating the expression of phase 2 GST, NQO1, and GPx2 [31], is consistent with the hypothesis that sulforaphane potentiates the phase 2 system while attenuating the phase 1 system [44,45].…”
mentioning
confidence: 99%
“…Nrf2 activation and the indirect antioxidant effects of sulforaphane appear to be ubiquitous; they have been observed in the liver [30][31][32]41,59,60], kidney [60], lungs [60][61][62][63], lens [58], central nervous system [49,60], immune system [50], choroid plexus [51], small intestine [9], large intestine [60], prostate [60], retinal pigment epithelial cells [34,39,64], corneal epithelial cells [55], astroglial cells [54], fetal neural crest cells [52], neuroblastoma cells [36], insulin-secreting pancreatic cells [65], differentiated peripheral blood neutrophils [53], endothelial cells [40], osteoblasts [37], and keratinocytes [33][34][35].…”
mentioning
confidence: 99%
“…17,18 It can damage the liver, spleen, circulating blood, kidney, genital systems, and bone marrow. [19][20][21][22] Delivery systems are innovative ways for administering to alleviate the disadvantages of the drug. [23][24][25] In order to reduce the adverse effects of TP, hydrophilic, biodegradable, and high drug-loading content efficiency drug carriers need to be developed.…”
mentioning
confidence: 99%